Semiotic change in modern and postmodern Time advertisements: an investigation based on systemic functional semiotics and social theory - Ferreira, Sidnéa Nunes (2012)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente, Florianópolis, 2011